Doctores, incentivos de titulación e impacto en la investigación: un panorama general de los profesores con doctorado en el sistema ecuatoriano de educación superior (Investigaciones) - Escobar Jiménez, Christian Manuel (2022)
This paper makes a descriptive and explanatory overview of the growth of number of university professors with a doctoral degree in the Ecuadorian Higher Education System, since 2013. It analyzes the legal framework and institutional incentives for the growth in the number of professors with a doctoral degree and includes a general review of the literature that considers their positive impact on the higher education system. This paper makes a general description which includes variables such as tenure, nationality, the doctoral program’s country and university, and the degree obtained. It then puts forward statistical regression models to explain and evaluate the impact of professors with a doctoral degree on research. It concludes that public policy has created a favorable environment, including perverse incentives, to pursue and obtain a doctoral degree and for welcoming professors from several countries. Additionally, it finds a positive correlation between the number of professors with a doctoral degree and the amount of research measured by number of indexed publications.